Implementation of Enterprise Risk Management (Erm) in Yayasan Yatim Mandiri Surabaya: Implementation of Enterprise Risk Management (Erm) in Yayasan Yatim Mandiri Surabaya - Hartomi Maulana; Naufalt Arkyananto (University of Darussalam Gontor, 2023)
Zakat is one of the Islamic philanthropy instruments that might used to reduce poverty in a country. Yayasan Yatim Mandiri Surabaya is engaged in the efforts of assisting orphans and the poor. Like other institutions, Yayasan Yatim Mandiri is also facing a risk while dealing with managing zakat funds. For this reason, this study attempts to analyze the application of risk management with ERM standards in Yayasan Yatim Mandiri. ERM standards discussed are the internal environment of the institution, identification of risk at the institution, measurement and assessment of risk, response to risks that occur, and risk control. This study uses a qualitative approach. The results of this study that the Yayasan Yatim Mandiri has comprehensively implemented risk management. it can be shown that the institution carries out direct supervision and evaluation of risks. this study has identified 24 types of risk identification, such as information system risk, human resource risk, and reputation risk. The study also found that the risk mitigation process is by increasing employee satisfaction and performance, improving information systems management, and increasing the reputation of risk in society